IMPROVING THE EARLY CHILDHOOD LANGUAGE SKILLS THROUGH SINGING ACTIVITY - Eka Rizki Amalia; Hasana Hasana (Prodi. Pendidikan Islam Anak Usia Dini, Institut Pesantren KH. Abdul Chalim, 2019)
During the children’s development, they will encounter a stage called the golden age. This stage is the most vital stage in children’s improvement since they will develop and grow quickly. This stage is the establishment for creating psychological, motoric, socio-emotional, religious, moral and language capacities. As to improvement of youngsters' language skills, it will be ideal on the off chance that it is led with incitement from the encompassing both from the guardians or family and the teachers. This literature study talks about the significance of directing and fostering the youngsters' language abilities from early childhood and exercises that can bolster the incitement procedure of early children’s language skills. The result of the literature review demonstrate that childrens’ language skills must be coordinated and supported since early childhood. An individual's language skills demonstrate his insight in communicating certain words and sentences normally and absolutely. For early childhood, the best stimulation is given by singing activities. Singing activities cannot be isolated from social relations, both with the surrounding, society, friends, and family. By singing activities, children will be acquainted with how to regard others, to place themselves in another condition, and train their capacity to communicate.